Purification and Characterization of Peroxidase From Anthracnose Disease Infected Papaya (Carica papaya L.) (Bangladesh Journal of Medical Biochemistry, 2014)
Peroxidase enzyme was isolated and purified from the pulp of disease infected ripen papaya of local variety by 90% ammonium sulphate precipitation, chromatography on DEAEcellulose followed by hydrophobic chromatography on Phenyl Sepharose CL-4B and the purifications achieved was about 7.2 fold with 2.5% recovery. The purified enzyme was homogeneous as judged by polyacrylamide slab gel electrophoresis. The purified enzyme had a Mr of about 55,000 and 50 000 as determined by gel filtration on Sephadex G-100 and SDS-PAGE, respectively. The molecular mass of the enzyme was found to be very similar under both reducing and non-reducing conditions indicating that the enzyme contains no subunit. The enzyme has the following characteristics: pH optima at 6.0, temperature optima around 38°C, enzyme activity was found to be strongly inhibited in the presence of potassium cyanide and Fe+2 while the activity was found to be remarkably increased in the presence of ammonium sulphate. The Km value for the peroxidase obtained with pyrogallol as substrate was 0.027 mM. DOI: http://dx.doi.org/10.3329/bjmb.v6i2.17643 Bangladesh J Med Biochem 2013; 6(2): 49-57